Corporate Governance and Firm Value in Mexico - Alberto Chong; Florencio Lopez-de-Silanes (Inter-American Development Bank, Research Department, 2006)
The objective of this paper is twofold. On one hand, we undertake an analysis of the recent evolution of capital markets and their effect on the availability of external financing in Mexico in the last two decades. On the other hand, based on a newly assembled firm-level data set on corporate governance and firm performance, we show that better firm-level corporate governance practices are linked to higher valuations, better performance and more dividends disbursed to investors. These results hold after controlling for endogeneity. Overall, the evidence shows that the Mexican legal environment poses serious problems for access to capital.
Keywords: 330